ANALYSIS OF GROUNDWATER SOFTENING METHODS - Rakhmatilllayev Yosunbek Ne’matilla o’g’li (Journal of new century innovations, 2023)
Abstract. In order to increase the demand for water for the population and indust rial enterprises and to solve this problem, in order to efficiently use groundwater, p rotect them from any pollution and compare methods used to date to soften hard w ater. To soften the groundwater, we offer a method of softening hard water using modern devices and filters created not only by our state, but also by foreign scientists. Such devices and filters differ from other types of hard water softening methods in their compactness and convenience and have many advantages.